BI-7 DAY REVERSE REPO RATE EXCHANGE RATE, MONEY SUPPLY, AND THE NUMBER OF SHARIA CAPITAL MARKET INVESTORS - Dahruji Dahruji; Camelia Lutfiana Mahmud (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
This study aims to analyze the influence of the variables BI 7-Day Reserve Repo Rate, Exchange Rate, and the Amount of Money in Circulation on investors in the Islamic capital market. The research method used is multiple linear regression using the t-test, F-test, and coefficient of determination (). The data used in this study is secondary data obtained from several data sources, namely IDX, Bank Indonesia, Badan Pusat Statistik, and CNBC Indonesia which includes data on the BI 7-Day Reserve Repo Rate, exchange rate, total money supply, and data on the number of investors. Islamic capital market in 2017-2021. The results of this study indicate that BI7DRR and Money Supply affect the Number of Islamic Capital Market Investors, while the Exchange Rate does not affect the Number of Islamic Capital Market Investors.